PROS AND CONS OF USING ALGORITHMIC MANAGEMENT IN HUMAN RESOURCE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The opportunities that Artificial Intelligence and the principles of Algorithmic management provide to modern managers bring undeniable advantages for the development of a competitive business in today's extremely difficult business environment. At the same time, however, the effect of their use should be carefully analysed from the point of view of the compliance of the employees opinion in the enterprise - mainly in line with the observance and guarantee of basic rights of the employees. In this regard, the European Parliament and the European Council launched a legislative initiative to define harmonized rules within the Community on the use of artificial intelligence. Concepts such as "algorithmic discrimination" were introduced quite purposefully at the regulation level, given the risk of possible abuses associated with the use of AI. This report aims to ascertain the views of employers and employees on the use of artificial intelligence in Human Resource Management. The report presents and analyses data from an empirical study conducted among managers and employees in leading ICT enterprises in Bulgaria. According to our responders, one of the biggest advantages of using AI in Human Resources Management is related to the elimination of subjectivity in performance evaluation and the possibility of fair play in the procedures of internal selection of employees. At the same time, employees with more experience (over 10 years) are more sceptical of the idea of their work performance being evaluated solely by AI, while younger workers show more trust in AI solutions. However, both managers and workers recognize that it is best for the final decision in determining career development to be made by a person, but justified by the analyses made by AI. The report draws conclusions and recommendations that can serve both researchers and business managers. Certainly, AI is yet to undergo a very large development and application, including in the Human Resource Management, but at the same time it should not be at the expense of affected rights.